Drosophila suzukii and Drosophila melanogaster prefer distinct microbial and plant aroma compounds in a complex fermented matrix. - Dzialo, M.C.; Arumugam, S.; Piampongsant, S.; Cool, L.; Vanderaa, C.; Herrera-Malaver, B.; Opsomer, T.; Dehaen, W.; Wenseleers, T.; Roncoroni, M.; Alawamleh, A.; Wäckers, F.; et al. (iScience, 2024)
Volatile aroma compounds are important chemical cues for insects. Behavioral responses to specific odors differ strongly between insect species, and the exact causative molecules are often unknown. Beer is frequently used in insect traps because it combines hundreds of plant and microbial aromas that attract many insects. Here, we analyzed responses of the pest fruit fly Drosophila suzukii and benign Drosophila melanogaster to beers with different chemical compositions. Using extensive chemical and behavioral assays, we identified ecologically relevant chemicals that influence drosophilid behavior and that induce different odor-evoked activity patterns in the antennal lobe of the two species obtained by functional imaging. Specific mixes of compounds increased the species-specificity and sex-specificity of lures in both laboratory and greenhouse settings. Together, our study shows how examining insect responses to highly complex natural mixtures of aroma compounds provides insight into insect-specific behavioral responses and also opens avenues for improved pest control.